Writing for digital media: Top Romanian Companies’ "About us" pages - Fărcașiu, Marcela Alina (Technium Social Sciences Journal, 2021)
This paper aims at examining a very fashionable and important topic nowadays, i.e. companies’ ?About Us’ pages, an ‘identity card’ through which companies must spark the potential customers’ interest in wanting to buy their products or try their services. To this purpose, 25 most valuable entrepreneurial Romanian companies’ ?About Us’ pages have been considered and analysed. Seeing that there are no specific guidelines concerning the content of such a page, the analysis has taken into account some criteria found in the literature relative to what a ‘perfect’ ‘About Us’ page must look like. The pages have been analysed and compared qualitatively and quantitatively based on these criteria. Screenshots of the pages have also been provided in order to exemplify the results